AB0584 DOES ANTI-ACID TREATMENT INFLUENCE DISEASE PROGRESSION IN SYSTEMIC SCLEROSIS INTERSTITIAL LUNG DISEASE (SSC-ILD)? DATA FROM THE GERMAN SSC-NETWORK. (2nd June 2020) - Kreuter, M.; Bonella, F.; Riemekasten, G.; Müller-Ladner, U.; Henes, J.; Siegert, E.; Guenther, C.; Koetter, I.; Blank, N.; Pfeiffer, C.; Schmalzing, M.; Zeidler, G.; et al.
Abstract : Background: Gastroesophageal reflux (GER) is common in SSc and thus treatment with anti-acid therapy (AAT) is frequent. An association between GER and the development / progression of SSc-ILD has been hypothesized. However, outcomes of AAT on disease progression in SSc-ILD has only sparsely been studied. Objectives: Methods: The German Network for Systemic Scleroderma (DNSS), which includes SSc pts. prospectively, was analyzed for SSc-ILD. Those without progression at ILD 1 st diagnosis were categorized in AAT vs. no-AAT users and disease outcome was assessed. Results: SSc-ILD was reported in 1165 (28.2%) out of 4131 pts. 712 of SSc-ILD pts had no disease progression at ILD 1 st diagnosis. 567 used AAT while 145 did not. Baseline characteristics were similar between groups with regards to age (mean 54.7 years), BMI, time since SSc diagnosis and immunosuppressant use. Significant differences in no-AAT vs. AAT were found for gender (male 18% vs. 25%, p=0.05), SSc subtype (p=0.002, diffuse more common in AAT), lung function (DLCO 66% vs. 58%, p=0.001; FVC 86% vs. 77%, p=0.001), mRSS (8 vs. 11.5, p<0.01), esophageal involvement (32% vs. 56%, p<0.01) and steroid use (30% vs. 43%, p=0.005). While mortality did not differ between groups (3.9%, p= 0.59), disease progression was more common in the AAT group than in no-AAT users (24.5% vs. 13%, p=0.03). Furthermore, there was a significant difference in decline of FVC≥10% with 30% in the AAT compared to 14% in no-AAT (p=0.018); a decline in DLCO≥15% was more common in the AAT group by trend (23% vs. 14%, p=0.087). Conclusion: While results may have partially been biased by differences in baseline characteristics, this current analysis disfavors the approach of AAT use for SSc-ILD. Disclosure of Interests: Michael Kreuter Grant/research support from: Roche, Boehringer, Consultant of: Roche, Boehringer, Speakers bureau: Boehringer, Roche, Francesco Bonella Grant/research support from: Boehringer, Consultant of: Boehringer, Roche, Bristol MS, Galapagos, Speakers bureau: Boehringer, Roche, Gabriela Riemekasten Consultant of: Cell Trend GmbH, Janssen, Actelion, Boehringer Ingelheim, Speakers bureau: Actelion, Novartis, Janssen, Roche, GlaxoSmithKline, Boehringer Ingelheim, Pfizer, Ulf Müller-Ladner Speakers bureau: Biogen, Jörg Henes Grant/research support from: Novartis, Roche-Chugai, Consultant of: Novartis, Roche, Celgene, Pfizer, Abbvie, Sanofi, Boehringer-Ingelheim, , Elise Siegert Grant/research support from: Actelion, Consultant of: AEC, Speakers bureau: NA, Claudia Guenther: None declared, Ina Koetter Grant/research support from: Novartis, Roche, Speakers bureau: Abbvie, Actelion, Celgene, MSD, UCB, Sanofi, Lilly, Pfizer, Novartis, Chugai, Roche, Boehringer, Norbert Blank Speakers bureau: Actelion, Roche, Boehringer, Pfizer, Chugai, Christiane Pfeiffer: None declared, Marc Schmalzing: None declared, Gabriele Zeidler: None declared, PETER KORSTEN Grant/research support from: Novartis, Juarms GmbH, Consultant of: Abbvie, Pfizer, Lilly, BMS, Speakers bureau: Abbvie, Pfizer, chugai, BMS, Lilly, Sanofi aventis, Laura Susok: None declared, Aaron Juche: None declared, Margitta Worm Consultant of: Mylan Gemany, Bencard Allergie, BBV Technologies S.A., Novartis, Biotest, Sanofi, Aimmune Therapies, Regeneron, Speakers bureau: ALK-Abello, Novartis, Sanofi, Biotest, Mylan, Actelion, HAL Allergie, Aimmune Bencard Allergie, Ilona Jandova: None declared, Jan Ehrchen: None declared, Cord Sunderkoetter: None declared, Gernot Keyszer: None declared, Andreas Ramming Grant/research support from: Pfizer, Novartis, Consultant of: Boehringer Ingelheim, Novartis, Gilead, Pfizer, Speakers bureau: Boehringer Ingelheim, Roche, Janssen, Tim Schmeiser Speakers bureau: Actelion, UCB, Pfizer, Alexander Kreuter Speakers bureau: Sanofi, Abbvie, Merck Sharp&Dohme, Boehringer, Kathrin Kuhr: None declared, Hanns-Martin Lorenz Grant/research support from: Consultancy and/or speaker fees and/or travel reimbursements: Abbvie, MSD, BMS, Pfizer, Celgene, Medac, GSK, Roche, Chugai, Novartis, UCB, Janssen-Cilag, Astra-Zeneca, Lilly. Scientific support and/or educational seminars and/or clinical studies: Abbvie, MSD, BMS, Pfizer, Celgene, Medac, GSK, Roche, Chugai, Novartis, UCB, Janssen-Cilag, Astra-Zeneca, Lilly, Baxter, SOBI, Biogen, Actelion, Bayer Vital, Shire, Octapharm, Sanofi, Hexal, Mundipharm, Thermo Fisher., Consultant of: see above, Pia Moinzadeh: None declared, Nicolas Hunzelmann Speakers bureau: Actelion, Boehringer